STATE OF FISHERIES RESOURCES IN LAGOS, OGUN AND OYO STATES, SOUTHWESTERN, NIGERIA - AJAYI, D. A; HASSAN, T.; TOLASE-FABUNMI, A. S; BOLATITO, A. O.; ALADELE, S. E; OMITOGUN, O. G; OLUFEAGBA, S. O. (Nigerian Journal of Fisheries, 2018)
This study investigated the status, development of new strains, management and constrains of fish culture systems in selected states of Southwestern Nigeria. Primary data were collected through a well-structured questionnaire from 300 fish farmers randomly selected from communities in the three study areas based on their fishing activities. The data were analyzed using descriptive statistical analysis. The investigation revealed that most of the fish farms were in existence for less than a decade. Farmers majorly reared Clariids (99.3%) and Cichlids (17.87 %). Lagos (114) and Oyo (120) States have the highest respondents using concrete pond while the earthen pond is most common in Oyo (97) and Ogun (90) states. Oyo state was the only location that reported the development of new strain; however, it has not yet been registered as it is still undergoing close evaluation. Smoking as a value addition (76.9%) was mostly adopted by farmers in all states. Challenges identified by a larger group of the farmers include lack of capital (83.8%) and the high cost of feeds (28.4%). It is suggested that governmental and non-governmental organizations should explore the possibilities of making available funds to overcome impediment limiting good performance and maximum output for sustainable aquaculture production in Nigeria.